Is there a patient population with squamous cell carcinoma of the head and neck region who might benefit from de-intensification of postoperative radiotherapy? - Onbasi, Yonca; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2019)
PURPOSE: The aim of this retrospective study was to evaluate the clinical outcome of a previously defined low-risk patient population with completely resected (R0) squamous cell carcinoma of the oral cavity, oropharynx, larynx (pT1-3, pN0-pN2b), hypopharynx (pT1-2, pN0-pN1), and the indication for postoperative radio(chemo)therapy. PATIENTS AND METHODS: According to predefined criteria, 99 patients with head and neck squamous cell carcinoma (SCC) who were treated at our institution from January 1, 2005 to December 31, 2014, were available for analysis. The Kaplan-Meier method was used for calculating survival and incidence rates. For univariate comparative analysis, the log-rank test was used for analyzing prognostic clinicopathologic parameters. RESULTS: Median follow-up was 67 months. Cumulative overall (OS) and disease-free survival (DFS) were 97.9%/94.7%/88.0% and 96.9%/92.6%/84.7% after 1, 2, and 5 years, respectively. Cumulative incidence of loco-regional recurrence (LRR), distant metastases (DM), and second cancer (SC) were 1.0%/1.0%/4.9%, 0.0%/3.4%/5.8%, and 2.1%/4.2%/13.1%, respectively. In univariate comparative analysis, location of the primary tumor in the oropharynx was a significant predictor for increased OS (p = 0.043) and DFS (p = 0.048). CONCLUSION: Considering the low disease relapse rates and high rates of therapy-induced late side effects, as well as the increased risk of developing SC, a prospective multicentric trial investigating de-escalation of radiotherapy in this clearly defined low-risk patient population was started and is still recruiting patients (DIREKHT-Trial, NCT02528955).
EVALuna2:184476